Application of MRI and biomedical engineering in speech production study - Sandra Moreira Rua Ventura (2009)
The speech production has always been a subject of interest both at morphologic and acoustic levels. This knowledge is useful for a better understanding of all the involved mechanisms, and for the construction of articulatory models. Magnetic resonance imaging (MRI) is a powerful technique that allows the study of the whole vocal tract, with good soft tissues contrast and resolution, and permits the calculation of area functions toward a better the understanding of this mechanism. Thus, our aim is to demonstrate the value and application of MRI in speech production study and its relationship with engineering, namely with biomedical engineering. After vocal tract contours extraction, data was processed for three-dimensional reconstruction culminating in models construction of some sounds of the European Portuguese. MRI provides useful morphologic data about the position and shape of the different speech articulators, and the biomedical engineering computational tools for its analysis.